64‐1: Lensless Microscope Using High‐Resolution Display. Issue 1 (29th May 2019) - Negoro, Yusuke; Yoneda, Seiichi; Nakagawa, Takashi; Shishido, Hideaki; Kobayashi, Hidetomo; Ikeda, Takayuki; Yamazaki, Shunpei
Abstract : We devise a lensless microscope as an application of high‐resolution displays. Images were taken at a resolution corresponding to the pixel size with the use of an existing display. An operation scheme for fast driving is suggested.